Line 1: Line 1:
== Z transform ==
+
== Z transform ==
 +
 
 +
----
  
 
Z transform is a general form of DTFT. If <span class="texhtml">''x''[''n'']</span> is a discrete periodic funtion, DFT of this function is <math>x[k] = \sum_{n=0}^{N-1} x[n]e^{-j\frac{{2\pi}k n}{N}}</math>  
 
Z transform is a general form of DTFT. If <span class="texhtml">''x''[''n'']</span> is a discrete periodic funtion, DFT of this function is <math>x[k] = \sum_{n=0}^{N-1} x[n]e^{-j\frac{{2\pi}k n}{N}}</math>  
Line 27: Line 29:
 
These are the examples of Z transform.  
 
These are the examples of Z transform.  
  
== 1. Unit step ==
+
----
 +
 
 +
== 1. Unit step ==
  
 
  When <math>x[n]=1 (n{\ge}0)</math>
 
  When <math>x[n]=1 (n{\ge}0)</math>
    <span class="texhtml">''x''[''n''] = 0(''n'' &lt; 0)</span>
+
  <span class="texhtml">''x''[''n''] = 0(''n'' &lt; 0)</span>
  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}1\cdot z^{-n}=\frac{1}{1-z^{-1}}</math>  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}1\cdot z^{-n}=\frac{1}{1-z^{-1}}</math>  
  
== 2. Power series ==
+
== 2. Power series ==
  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}a^{n} z^{-n}=\frac{1}{1-az^{-1}}</math>  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}a^{n} z^{-n}=\frac{1}{1-az^{-1}}</math>  
  
== 3. Exponential funtion ==
+
== 3. Exponential funtion ==
  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}e^{-an} z^{-n}=\sum_{n=0}^{\infty}[e^{-a} z^{-1}]^{n}=\frac{1}{1-e^{-a}z^{-n}}</math>  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}e^{-an} z^{-n}=\sum_{n=0}^{\infty}[e^{-a} z^{-1}]^{n}=\frac{1}{1-e^{-a}z^{-n}}</math>  
  
== 4. Sinusoidal function ==
+
== 4. Sinusoidal function ==
  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}\frac{e^{jn{\omega}} -e^{-jn{\omega}}} {2j} z^{-n}</math> <math> =\frac{1}{2j} (\frac{1}{1-e^{j\omega}z^{-1}}-\frac{1}{1-e^{-j\omega}z^{-1}})</math> <math> =\frac{1}{2j} (\frac{-e^{-j\omega}z^{-1}+e^{j\omega}z^{-1}}{1-e^{-j\omega}z^{-1}-e^{j\omega}z^{-1}+z^{-2}})</math> <math> =\frac{z^{-1}sin(\omega)}{1-2z^{-1}cos(\omega)+z^{-2}}</math>  
 
<math>X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}\frac{e^{jn{\omega}} -e^{-jn{\omega}}} {2j} z^{-n}</math> <math> =\frac{1}{2j} (\frac{1}{1-e^{j\omega}z^{-1}}-\frac{1}{1-e^{-j\omega}z^{-1}})</math> <math> =\frac{1}{2j} (\frac{-e^{-j\omega}z^{-1}+e^{j\omega}z^{-1}}{1-e^{-j\omega}z^{-1}-e^{j\omega}z^{-1}+z^{-2}})</math> <math> =\frac{z^{-1}sin(\omega)}{1-2z^{-1}cos(\omega)+z^{-2}}</math>  
  
== Properties of Z transform ==
+
----
 +
 
 +
== Properties of Z transform ==
  
== 1. Linearity ==
+
== 1. Linearity ==
  
<span class="texhtml">''Z''(''a''''x''[''n''] + ''b''''y''[''n'']) = ''a''''X''(''z'') + ''b''''Y''(''z'')</span>  
+
<span class="texhtml">''Z''(''a''''x'''''<b>[''n''] + ''b'''''y''[''n'']) = ''a''''X'''''<b>(</b>'''''z'') + ''b''''''''Y''(''z'')</span>  
  
== 2. Time Delay ==
+
== 2. Time Delay ==
  
 
<math>Z(x[n-k])=z^{-k}[X(z)+\sum_{n=1}^{k}x[-n]z^{n}]</math>  
 
<math>Z(x[n-k])=z^{-k}[X(z)+\sum_{n=1}^{k}x[-n]z^{n}]</math>  
  
== 3. Time Advance ==
+
== 3. Time Advance ==
  
 
<math>Z(x[n+k])=z^{k}[X(z)-\sum_{n=0}^{k-1}x[n]z^{-n}]</math>  
 
<math>Z(x[n+k])=z^{k}[X(z)-\sum_{n=0}^{k-1}x[n]z^{-n}]</math>  
  
== 4. Time Convolution Theorem ==
+
== 4. Time Convolution Theorem ==
  
 
<span class="texhtml">''Z''(''x''[''n''] * ''y''[''n'']) = ''X''(''z'')''Y''(''z'')</span>
 
<span class="texhtml">''Z''(''x''[''n''] * ''y''[''n'']) = ''X''(''z'')''Y''(''z'')</span>

Revision as of 10:07, 16 October 2010

Z transform


Z transform is a general form of DTFT. If x[n] is a discrete periodic funtion, DFT of this function is $ x[k] = \sum_{n=0}^{N-1} x[n]e^{-j\frac{{2\pi}k n}{N}} $

Let's say x[n] is discrete nonperiodic function. Nonperiodic function is also a function with period $ \infty $. Therefore DTFT of this function can be DFT with $ N=\infty $. $ \lim_{N\to\infty}\sum_{n=0}^{N-1}x[n]e^{-j\frac{{2\pi}k n}{N}}=\sum_{n=0}^{\infty}x[n]e^{-j{\omega}n} $, where $ \omega=\lim_{N\to\infty}\frac{{2\pi}k}{N} $

$ X(w)=\sum_{n=0}^{\infty}x[n]e^{-j{\omega}n} $ ---> DTFT

The difference between DFT and DTFT is that DFT has a discrete function with k and DTFT is a continuous function with ω.

Let's generalize the DTFT. By substitution of real value frequency ω into complex frequency value s = σ + iω, DTFT is now discrete function of Laplace transform.

$ X(s)=\sum_{n=0}^{\infty}x[n]e^{-sn} $ ---> Laplace Transform

When es = z, it is a Z transform.

$ X(z)=Z[x[n]]=\sum_{n=0}^{\infty}x[n]z^{-n} $ ---> Z Transform

The first reason why we are using z transform instead of laplace is becuase it is easier to calculate the geometric series by substitution of variable from s to z. Also properties of power series with differential equation is useful.

As the variable es is substituted with z, region of convergence changes from the complex plane. The region of convergence in the complex plane for Z transform is outside region of a unit circle | z | = r = 1, where r is radius of a unit circle.

Inverse Z transform can be stated as

$ x[n]=\frac{1}{j{2\pi}}\oint{X(z)z^{n-1}dz} $

These are the examples of Z transform.


1. Unit step

When $ x[n]=1 (n{\ge}0) $
  x[n] = 0(n < 0)

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}1\cdot z^{-n}=\frac{1}{1-z^{-1}} $

2. Power series

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}a^{n} z^{-n}=\frac{1}{1-az^{-1}} $

3. Exponential funtion

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}e^{-an} z^{-n}=\sum_{n=0}^{\infty}[e^{-a} z^{-1}]^{n}=\frac{1}{1-e^{-a}z^{-n}} $

4. Sinusoidal function

$ X(z)=\sum_{n=0}^{\infty}x[n]z^{n}=\sum_{n=0}^{\infty}\frac{e^{jn{\omega}} -e^{-jn{\omega}}} {2j} z^{-n} $ $ =\frac{1}{2j} (\frac{1}{1-e^{j\omega}z^{-1}}-\frac{1}{1-e^{-j\omega}z^{-1}}) $ $ =\frac{1}{2j} (\frac{-e^{-j\omega}z^{-1}+e^{j\omega}z^{-1}}{1-e^{-j\omega}z^{-1}-e^{j\omega}z^{-1}+z^{-2}}) $ $ =\frac{z^{-1}sin(\omega)}{1-2z^{-1}cos(\omega)+z^{-2}} $


Properties of Z transform

1. Linearity

Z(a'x[n] + by[n]) = a'X<b>(z) + b'''Y(z)

2. Time Delay

$ Z(x[n-k])=z^{-k}[X(z)+\sum_{n=1}^{k}x[-n]z^{n}] $

3. Time Advance

$ Z(x[n+k])=z^{k}[X(z)-\sum_{n=0}^{k-1}x[n]z^{-n}] $

4. Time Convolution Theorem

Z(x[n] * y[n]) = X(z)Y(z)

Alumni Liaison

has a message for current ECE438 students.

Sean Hu, ECE PhD 2009